EUROPEAN ORIENTATION OF THE ECONOMY OF UKRAINE: HISTORICAL FEATURES AND CURRENT TRENDS IN THE CONTEXT OF STRATEGIC DECISIONS - I. Novikova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article highlights the historic features and modern trends of European orientation of Ukraine's economy. The analyzed dynamics of export / import of Ukrainian goods and services to / from the eurozone countries and means of stimulating export activities, in particular through the creation and implementation of innovative products. Was investigated the problems arising from the implementation of the strategic European principles in Ukraine. Provided recommendations to overcome barriers to European integration of the national economy.